2023
DOI: 10.1097/dss.0000000000003655
|View full text |Cite
|
Sign up to set email alerts
|

Publication Productivity Using H-Index to Evaluate Academic Success Among Fellowship-Trained Mohs Surgeons

Abstract: BACKGROUND The h-index is a measure of research achievement using not only the number of publications of an individual, but also the impact of the publications. OBJECTIVE The objective of this study is to evaluate the h-indices of Mohs surgeons within a variety of practice settings. MATERIALS AND METHODS A list of all American College of Mohs Society (ACMS) members with corresponding fellowships years were collected using the ACMS membership directory. Publicly available demographic information was obtained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…30,31 The authors found that H-index was similar between female and male MMS FDs after adjusting for years in practice and academic rank, indicating that women and men are equally qualified for their positions. Marion and colleagues 32 found that the H-indices of academic Mohs surgeons were higher than that of private practice Mohs surgeons. In contrast, the authors found that among FDs, there was no significant difference in H-index across program types, suggesting that research plays a large role in the FD career regardless of practice type.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…30,31 The authors found that H-index was similar between female and male MMS FDs after adjusting for years in practice and academic rank, indicating that women and men are equally qualified for their positions. Marion and colleagues 32 found that the H-indices of academic Mohs surgeons were higher than that of private practice Mohs surgeons. In contrast, the authors found that among FDs, there was no significant difference in H-index across program types, suggesting that research plays a large role in the FD career regardless of practice type.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the current MMS FDs work at academic institutions, in contrast to the overall MMS workforce, which predominates the private practice sphere. 32 Draws of the academic setting may include intellectual stimulation, teaching prospects, and collaboration opportunities, whereas deterrents may include decreased autonomy. 33 The predominance of MMS FDs in the academic setting may be expected because FDs are not only greatly involved in teaching and research but also have the unique position as leaders to have autonomy over their own programs.…”
Section: Discussionmentioning
confidence: 99%
“…Key findings include a higher h-index in academic (associated with a dermatology residency program or Mohs fellowship) and combined (academic appointment plus non-academic appointment) settings compared with nonacademic settings. 1 Therefore, protected academic time in academic and private practices may help to promote academic productivity and contribute toward advancing the field. Of the 1150 ACMS members reviewed, 122 (10.6%) were employed in an academic setting.…”
mentioning
confidence: 99%
“…Marion and colleagues 1 ' article, “Publication Productivity Using H-index to Evaluate Academic Success Among Fellowship-Trained Mohs Surgeons,” analyzes publication productivity among Mohs surgeons. The authors focused on the h-index as a metric for publication productivity among 1150 ACMS members.…”
mentioning
confidence: 99%